Football and COVID-19: the effects of the pandemic on training and performance of South American and Brazilian referees - Boschilia, B.; Lima Moraes, L. C.; Junior, W. M. (Soccer & Society, 2020)
The effects caused by the COVID-19 pandemic impacted the most diverse areas of society, including sport. During the quarantine period, there were several movements to confront the pandemic, which included advances, setbacks and attempts to resume daily activities and sports. In the sports scene, we observed the suspension, postponement or cancellation of the most important international level competitions; football and those involved in it were aware of this process. Considering this, we seek to present the training and maintenance of the activities of football referees during quarantine, projecting a future scenario by fostering debates about what might be the possible changes in the preparation and performance of these officials in South America and, specifically, in Brazil, after the COVID-19 pandemic.